Online Newspapers in the Age of the Web 2.0 - Rabah, Saddek (ALBAHITH ALALAMI, 2014)
If we go beyond the technical aspects of the Web 2.0, and we focus specifically on its interactive characteristics, we may say it represents not only a fundamental shift in the structure of the press institutions and its practices but also a shift in the relationships that existed, previously, between the press and the audience. Web 2.0 has enabled the newspapers to renovate their representations and practices of the profession and opens to the new horizons either in terms of readership or advertising revenues. Parallel to that it also has empowered the user to transcend the passivity he has always been confined in and has become a more active participant in the creation and generation of media contents even though this practice is somewhat different from one newspaper to another.This paper investigates the actual trend and attitude of the online newspapers towards Web 2.0 and focuses on identifying to what extent these newspapers have successfully adopted the features and mechanisms governing this web. It seeks to accomplish this endeavor through an investigative approach, coupled with some critical and interpretive views emanating from a bulk of research related to this question. The paper assumes that online newspapers have not adopted the same position regarding web 2.0. This position differs from one cultural space to another. Some actors prefer keeping on a tradition vision of the craft, while others, considered as the pioneers and the most innovative, accept to implement the considerable potentialities offered to them by Web 2.0.